Risk Management and Public Administration for Entities of Urban Public Transport: The Case of Silesian Voivodeship, Poland - Grzegorz DYDKOWSKI; Wiktoria GALECKA; Anna URBANEK (Communications of International Proceedings, 2023)
The paper presents risks related to the organisation of urban public transport, broken down to entities and the level of city transport policy, public transport organiser, and operators providing services. The risks were identified for a model, in which gross costs contracts are concluded based on the example of the central part of the Silesian Voivodeship, using selected methods for knowledge gaining about the organisation, analyses of documents and case studies. Also basic rules of risk allocation have been presented, so as to reduce the probability of their occurrence, and the possible effects, if any.
Keywords: Risk; Urban Public Transport